Risk processes with dependent claim size and claim occurrence times - Heilpern, Stanisław (Silesian Statistical Reviev, 2012)
The paper is devoted to the risk process, when the claim amount and the interclaim times may be dependent. The impact of the degree of dependence on the probability of ruin is investigated. The three cases are studied: the case when the joint distribution has the bivariate exponential distribution and when the dependent structure is described by FGM and Clayton copulas. The comparison with the previous study is made too
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2012, Nr 10 (16), s. 57-68
Keywords: risk process; dependence; probability of ruin; copula; proces ryzyka; zależność; prawdopodobieństwo ruiny; funkcje łączące